PENGARUH PROMOSI DAN PELAYANAN TERHADAP MINAT KONSUMEN PADA PRODUK PERABOT (Kasus Kindy Jati Gallery Pekanbaru) - Aprizal Putra; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine how the influence of promotion (inform, introduce, persuade, and action) and Services (Tangibles, Ephaty, Reliaility, Responsiveness and Assurance) against the interests of consumers (Attention, interest, Desire, and Action) on Kindy teak Gallery Pekanbaru, The population in this study is consumers who buy teak furniture Kindy Gallery Pekanbaru with 100 samples, sampling using the formula slovin. The data collection of primary data research, with questionnaires as an instrument of research and secondary data from company archives, data analysis used is by using multiple linear regression, determination test, t test and f SPSS.From the results of data analysis include validity, reliability, and multiple linear regression, t test research results showing the calculation of the t (3.730)> t table (1.985) and Sig. (0.000) <0.05. This means that variables significantly influence the Promotion of Consumer Interests.And the results showed the calculation of the t (7.211)> t table (1.985) and Sig. (0.000) <0.05. This means that variables significantly influence the performance of Consumer Interests and based on the test concluded that the simultaneous sale and service together significant effect on consumer interest with 74.7% a big influence on teak Kindy Gallery Pekanbaru.Keywords: Promotion, Services, Consumer Interest